Learner variables in the development of intercultural competence: A synthesis of home and study abroad research - Tajeddin, Zia; Khanlarzadeh, Neda; Ghanbar, Hessameddin (Studies in Second Language Learning and Teaching, 2022)
To provide insights into a wide array of individual learner variables implicated in intercultural education in home and study abroad contexts, this study systematically reviewed the effects of such variables on the development of intercultural competence. The corpus consisted of 56 journal articles published over the past two decades (2000-2020). The purpose of this study was to explore: (a) learner variables that were described in research on intercultural competence, including, inter alia, their age, gender, first language (L1) background, proficiency level, and attitudinal orientations; (b) settings in which learners’ intercultural development was studied, including both home contexts and study abroad contexts; and (c) effects of learner variables on the development of their intercultural competence. The results of this synthesis indicate that a growing number of studies have started to document intercultural instruction in both home and study abroad contexts. They show how learner variables were considered in conducting these studies and how variation in these variables impacted the effectiveness of instruction that targeted intercultural competence. The findings can considerably broaden our understanding of both opportunities and constraints in intercultural education in terms of learner variables and in particular variables that make the most contribution to intercultural development in home and study abroad contexts.